Peptidylarginine deiminase 2 citrullinates MZB1 and promotes the secretion of IgM and IgA - Geary, Benjamin; Sun, Bo; Tilvawala, Ronak R.; Barasa, Leonard; Tsoyi, Konstantin; Rosas, Ivan O.; Thompson, Paul R.; Ho, I-Cheng (Frontiers in Immunology, 2023)
MZB1 is an endoplasmic reticulum residential protein preferentially expressed in plasma cells, marginal zone and B1 B cells. Recent studies on murine B cells shows that it interacts with the tail piece of IgM and IgA heavy chain and promotes the secretion of these two classes of immunoglobulin. However, its role in primary human B cells has yet to be determined and how its function is regulated is still unknown. The conversion of peptidylarginine to peptidylcitrulline, also known as citrullination, by peptidylarginine deiminases (PADs) can critically influence the function of proteins in immune cells, such as neutrophils and T cells; however, the role of PADs in B cells remains to be elucidated. In an unbiased analysis of human citrullinome, we found that MZB1 was preferentially enriched in the pool of citrullinated lung proteins obtained from patients with rheumatoid arthritis-associated interstitial lung disease (RA-ILD). The citrullination of MZB1 was confirmed with mass spectrometry, in vitro citrullination, and binding by phenylglyoxal in the absence or presence of a PAD2-specific inhibitor AFM-30a. Ablation or pharmacological inhibition of PAD2 in primary human B cells attenuated the secretion of IgM and IgA but not IgG or the differentiation of IgM or IgA-expressing plasmablasts, recapitulating the effect of ablating MZB1. Furthermore, the physical interaction between endogenous MZB1 and IgM/IgA was attenuated by AFM-30a. Taken together, our data confirm the function of MZB1 in primary human plasmablasts and suggest that PAD2 promotes IgM/IgA secretion by citrullinating MZB1, thereby contributing to the pathogenesis of rheumatoid arthritis and RA-ILD.